Can Medicaid Claims Validly Ascertain Foster Care Status?. (August 2017) - Raghavan, Ramesh; Brown, Derek S.; Allaire, Benjamin T.
Medicaid claims have been used to identify populations of children in foster care in the current literature; however, the ability of such an approach to validly ascertain a foster care population is unknown. This study linked children in the National Survey of Child and Adolescent Well-Being-I to their Medicaid claims from 36 states using their Social Security numbers. Using this match, we examined discordance between caregiver report of foster care placement and the foster care eligibility code contained in the child's Medicaid claims. Only 73% of youth placed in foster care for at least a year displayed a Medicaid code for foster care eligibility. Half of all youth coming into contact with child welfare displayed discordance between caregiver report and Medicaid claims. Children with emergency department utilization, and those in primary care case management health insurance arrangements, had the highest odds of accurate ascertainment. The use of Medicaid claims to identify a cohort of children in foster care results in high rates of underascertainment. Supplementing administrative data with survey data is one way to enhance validity of ascertainment.